Activated peroxydisulfate by sorghum straw-based biochar for enhanced tartrazine degradation: Roles of adsorption and radical/nonradical processes. (1st January 2023) - Chen, Xiaojuan; Zhou, Yu; Li, Jiesen; Pillai, Suresh C.; Bolan, Nanthi; He, Juhua; Li, Ning; Xu, Song; Chen, Xin; Lin, Qinghua; Wang, Hailong
Abstract: Biochar obtained from biomass waste through pyrolysis has significant potential in wastewater treatment due to its large specific surface area and multi-functional active sites. In current study, sorghum straw (SS) was pyrolyzed to prepare various biochar under nitrogen atmosphere. Adsorption kinetics of prepared biochar toward tartrazine (TTZ) was systematically investigated, and the biochar was also characterized by using multiple techniques to explore the contribution of physicochemical properties to adsorption. Then, the biochar with optimum TTZ adsorption performance, was also applied as a catalyst for peroxydisulfate (PDS) activation to degrade TTZ. Factors including PDS concentration, solution pH, and reaction temperature were examined. The optimized degradation rate constant of TTZ (1.1627 min −1 ) was achieved under the conditions at 2 mM PDS, pH of 3, and 23 °C. In addition, the free radical trapping experiments and EPR spectra revealed that the reactive substances of electron ( e − ), 1 O2, SO4 −, O2 −, and OH contributed to TTZ degradation. Density Functional Theory (DFT) also concluded that the atoms C(6), O(12), N(16), N(17), C(18) and N(22) in TTZ molecule showed larger f 0 values which are vulnerable to radical attack. Therefore, the synergistic mechanism embodying adsorption and radical/non-radical processes were proposed. Besides, the degradation pathways of TTZ were identified with the aid of HPLC/MS technique, indicating that multiple reaction processes containing the symmetrical cleavage of azo bonds, the asymmetrical cleavage of C–N, desulfonation, and benzene-like structure cracking were involved. Therefore, this study provides a simple and effective catalytic system for TTZ degradation, and also realizes the resource utilization of solid waste. Graphical abstract: Image 1 Highlights: Sorghum straw-based biochar showed good adsorption capacity to tartrazine (TTZ). TTZ could be well degraded through the catalysis of biochar/PDS system. The degradation activation energy of TTZ was greatly decreased. TTZ removal was attributed to the synergism of adsorption and radical/non-radical processes. Toxicity of most degradation products (intermediates) was lower than that of TTZ.